Kajian Model Fisik Pengaruh Freeboard dan Susunan Buis Beton Sebagai Pemecah Gelombang Tenggelam Ambang Rendah (Pegar) Dalam Mereduksi Gelombang - Zulkarnain Zulkarnain; Nadjadji Anwar (Borneo Engineering : Jurnal Teknik Sipil, 2017)
The Research Center and Development of Water (Puslitbang) is currently developing the Submerged Breakwater in shallow sea area (PEGAR). The author is interested to examine the material that easily obtained in the field of RCP concrete cylinder. The observation is how it to be ability in function as submerged breakwater an go green and low cost. The physical model of wave transmission test is how the response to the structure in ability to damping of wave as the breakwater function. In this research breakwater used is submerged breakwater type by using concrete cylinder (buis beton). The purpose from this research is to know how the response of breakwater structure to the waves through it, with some variation of the structure by creating a structure with three variations of the arrangement and freeboard that is the relative depth with the crest width is constant. The wave generated test in this study is using regular waves in wave flume at FTSP Civil Engineering Department of Institute Technology Ten November. From the analysis of the effect of the installation of submerged breakwater by using concrete cylinder to the wave damping value, it can be concluded that the factors that are very influential is the freeboard and the composition of concrete cylinder. Scenario A (rigid vertical massive) is capable of producing the smallest value of kt is 0.33. As for scenario B (rigid horyzontal massive) with a damping value of 0.5, while the scenario C (rigid permeable) is only able to produce kt value of 0.71. Scenario A is better than scenario B and C Because the position of arrangement of A is very good used to damp wave in small or big freeboard conditions.